Habitat selection in translocated gregarious ungulate species: An interplay between sociality and ecological requirements1. Issue 4 (25th February 2013) - Scillitani, Laura; Darmon, Gaëlle; Monaco, Andrea; Cocca, Giampaolo; Sturaro, Enrico; Rossi, Luca; Ramanzin, Maurizio
Abstract: The adaptation of translocated organisms to a new environment in the first years after their release is crucial in translocation programs because it may affect survival and reproductive success. Therefore, identifying the factors determining resource selection by the relocated animals is essential to improve the planning and the outcome of such programs. Using data collected in 2006–2009 in the framework of a restocking program, we studied the temporal variation of habitat selection in 14 translocated Alpine ibex ( Capra ibex ) during the year of their release and the following 3 years. We hypothesized a progressive adaptation of the translocated individuals, highlighted by a gradual decrease in the dissimilarities between translocated and resident individuals in ecological characteristics and social behavior. We tested the differences in habitat selection and home range size between the translocated and resident individuals and compared the spatial overlap between the groups. As expected, the dissimilarities decreased annually. The translocated and resident ibex almost immediately selected the same habitat resources, but the translocated individuals required 3 years to become fully socially assimilated. Our results indicated that habitat selection by gregarious species in a new environment is primarily driven by specific ecological requirements and that sociality plays a significant role. The translocated individuals tended to colonize areas already occupied by residents, either to fulfill social requirements and/or because the location of resident individuals may indicate high‐quality habitat. This pattern of behavior must be considered in the planning of translocation programs because habitat selection can affect the outcomes of the programs. © 2013 The Wildlife Society.